Los Derechos Constitucionales de Niños Niñas y Adolescentes no se hacen efectivos en relación a la Pensión Alimenticia que deben los Padres que están en el Extranjero, debiendo Legislarse para que regresen y Trabajen conjuntamente con el Estado y cumplan la obligación Legal - Carrillo Cando, Dennise María (2017)
The National Constitution of the Ecuadorian Republic establishes the children and adolescents right are inalienable and parents have the obligation to provide their children with all the necessary resources for daily sustenance. Nevertheless, this law is currently violated when the parents are abroad and they do not fulfill their legal obligation creating in this way a huge number of economic, social, and affective problems, where minors are the only ones really harmed. When we are talking about alimony, it has to be understand about the indispensable money which every child needs either for daily sustenance, aspects such as: education, dress, room and medical care, this is why the State through its competent authorities is obliged to guarantee these laws and rights must be fulfilled in favor of the fed, thus fulfilling what is established in The National Constitution of the Ecuadorian Republic, and supported by international agreements and other laws. The Children and Adolescents Organic Code fully guarantee the right to food for children and adolescents, understanding this right is born of the relation parent-subsidiary, with alimony being a way to fulfill their obligation that each one of the parents. Although constitutional norms, international agreements and other laws guarantee the right to food of the daughters and sons from parents abroad, however this right is not effectively enforced affecting the principle of the best 5 interest of the child and Integral development of the same ones. The violation of this right in which I have made mention in the previous paragraphs happens because in our days there is no clear rule(law) in which this collection takes effect; Being this legal insufficiency which causes the problem which is addressed in this research work, which is entitled: "The Constitutional Rights of children and adolescents do not become effective in relation to the alimony that the parents who are in The foreigner must legislate so that they return and work jointly with the State and fulfill the legal obligation " Finally, the present researching is focused on the aim of a legal proposal which must avoid the non-payment of maintenance payments with the help of the State that the parents when they are abroad and do not fulfill their obligation return to their country and are inserted In a Labor Regime supervised by the same, that allows to pay food and to fulfill with the obligation to feed them.